Increasing Tourist Visit Intention to Bali Zoo Through Social Media Marketing, Tourist Facilities and Tourist Destination Image - Yuliani, Ni Kadek Tiara; Ardani, Wayan; Yusmini, Ni Made (Peneliti.net, 2024)
This research aims to explore the influence of social media marketing, tourist facilities and destination image on tourist interest in visiting Bali Zoo. The research method used is an associative method with a quantitative approach. The survey was conducted using a questionnaire to tourists who had visited Bali Zoo at least once, with a sample size of 120 respondents. The data collected was then tested for validity, reliability, and analyzed using descriptive analysis, prerequisite tests, multiple regression, and hypothesis testing. The research results show that the better the implementation of social media marketing, the higher the interest in visiting Bali Zoo. Likewise, the facilities provided and the image of the tourist destination, both of which have a positive influence on interest in visiting. Overall, social media marketing, tourist facilities, and tourist destination image simultaneously have a significant effect on interest in visiting Bali Zoo. This research provides better understanding of the factors that influence tourist interest in visiting, as well as the importance of effective management and promotion in increasing the attractiveness of tourist attractions such as the Bali Zoo.